Self-Compassion as a Mediator Between Self-Criticism and Physical Symptom Reporting - Yousefi, Zahra; Golparvar, Mohsen (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to investigate whether self-compassion mediates the relationship between self-criticism and physical symptom reporting in a sample of  Iranian adults. A descriptive correlational research design was employed with a sample of 435 participants selected based on the Morgan and Krejcie sample size table. Participants completed three standardized self-report instruments: the Levels of Self-Criticism Scale (LOSC), the Self-Compassion Scale (SCS), and the Patient Health Questionnaire-15 (PHQ-15) for physical symptom reporting. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation analysis, and AMOS-21 was used to conduct Structural Equation Modeling (SEM) to evaluate the mediation model. The results revealed significant correlations between all study variables. Self-criticism was positively correlated with physical symptom reporting (r = .47, p < .001) and negatively correlated with self-compassion (r = –.53, p < .001). Self-compassion was also negatively associated with physical symptom reporting (r = –.45, p < .001). SEM analysis indicated that the model demonstrated good fit (χ²/df = 2.10, CFI = .96, RMSEA = .051). Direct effects were significant from self-criticism to physical symptom reporting (β = .29, p < .001), from self-criticism to self-compassion (β = –.53, p < .001), and from self-compassion to physical symptom reporting (β = –.26, p < .001). The indirect effect of self-criticism on physical symptoms through self-compassion was also significant (β = .14, p = .002), confirming partial mediation. The findings suggest that self-compassion serves as a psychological buffer that partially mediates the impact of self-criticism on physical symptom reporting. Enhancing self-compassion may reduce the somatic burden of individuals prone to self-critical thinking, offering valuable implications for psychological interventions and health promotion.